2017
DOI: 10.1187/cbe.16-09-0281
|View full text |Cite
|
Sign up to set email alerts
|

Using Next-Generation Sequencing to Explore Genetics and Race in the High School Classroom

Abstract: Modern genetics relies on cutting-edge sequencing and bioinformatics technologies. A high school experiment that explores current sequencing techniques in the context of race and genetics is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Implementation of personal genomics analysis into the classroom has occurred at numerous schools including Stanford, Pennsylvania State University, University of Pennsylvania, Duke and others [ 20 , 45 , 46 ]. Analysis of genetics and race using next generation sequencing has recently been used successfully in high school classrooms to improve student learning [ 47 ]. While personal genomics is now a mature field, personal microbiome analysis is a much younger field with less known regarding data interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…Implementation of personal genomics analysis into the classroom has occurred at numerous schools including Stanford, Pennsylvania State University, University of Pennsylvania, Duke and others [ 20 , 45 , 46 ]. Analysis of genetics and race using next generation sequencing has recently been used successfully in high school classrooms to improve student learning [ 47 ]. While personal genomics is now a mature field, personal microbiome analysis is a much younger field with less known regarding data interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, many exciting contemporary biology topics that would produce student interest in STEM do not necessarily fit into the NGSS, including epidemiology (Dumais and Hasni, 2009), stem cell biology (Salli et al, 2007), neuroscience (Gage, 2019), genetics (Yang et al, 2017), gene editing/synthetic biology (Stark et al, 2019), bioinformatics (Kovarik et al, 2013), and integrating interdisciplinary topics like the effects of climate change on human health (Nagle, 2013). Trying to engage students by teaching contemporary biology poses problems of how to integrate such topics into the existing content standards.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most teams score within a few points of each other, indicating that although there is a "winner," all students have acquired new knowledge and understanding during the lab. Research on a similar program has demonstrated that after a hands-on biotechnology lab experience, students show an improved attitude towards science and scientific research, independent of content knowledge gains (Jarrett et al, 2016;Yang et al, 2017).…”
Section: Resultsmentioning
confidence: 99%